Analisis Metode Belajar Kosa Kata - Robihim Robihim (Lingua Cultura, 2008)
Many jobs fields needed foreign language skills, such as Japanese. To comprehend the Japanese text, people must understand Japanese characters like Hiragana, Katakana, and Kanji because three of them were always used in Japanese text. Learning Hiragana and Katakana usually were taught in elementary level then secondary and high levels have more Kanji usages. Learning Japanese kanji meant learning vocabulary too. But, learning kanji had to be continuos and routine, because kanji had more than one meanings. Kanji did not only one meaning. So, we should know the meaning of the interrelated other kanji writing. To make easy in reading to read Japanese texts, certainly we should know kanji characters and the meanings.